Characterization of male Huacaya alpaca (Vicugna pacos) fibre from Cajamarca, Peru - Liñan Sanchez, Brey (2025)
Early fibre characterization is essential to allow alpaca breeders to select outstanding males and establish proper breeding programs. In this work, the characteristics of the fibre in male Huacaya alpacas from the province of Cajamarca were determined. The alpacas studied were from two alpaca companies. Parameters evaluated included Mean Fibre Diameter (MDF), Coefficient of Variation of Fibre Diameter (CVDF), Comfort Index (CI), Curvature Index (ICur) and Fineness to Yarn (FiHi)). These characteristics were analyzed in relation to the origin and age of 80 male alpacas from 1 to 3 years old using the Laserscan equipment. The overall MDF was 22.6µm, the CVDF was 22.4%, the FiHi had a value of 22.3µm, the ICur a value of 53.3°/mm, and the CI was 89.5%. In addition, it was found that the origin of the alpacas significantly affected the fibre diameter and the fineness of the yarn; while, the age of the animals significantly influenced the fibre diameter, yarn fineness, curvature index and comfort index. The results obtained indicate that male alpacas from Cajamarca have a good genetic potential in fine fibre quality. As a recommendation for breeders, it is suggested to evaluate the diameter of the fibre from 12 to 36 months of age, with the purpose of selecting future breeding males that can improve the characteristics of the fibre.